2015
DOI: 10.1007/s11277-015-2743-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MAC Strategies for Underwater Applications

Abstract: This study aims at analyzing the performance of protocols designed for the control of Medium Access in the underwater environment using Underwater Acoustic Wireless Sensor Networks (UW-ASNs). Oceans today, are playing an eminent part in monitoring climate, storing and releasing Carbon dioxide, supplying foodstuffs, and shipping. The sectors that can benefit most from this research are industries dealing with oil and gas, fisheries, UW instrumentation, armed forces, research and exploration bureaus, etc. Existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
5
0
3
Order By: Relevance
“…Bir düğümün biri çok yakın diğeri çok uzak komşularının olduğu durumlarda farklı paket gecikmeleri yüzünden MACA'da çarpışmalar meydana gelebilir. [9]. Bu sorunun üstesinden gelmek için FAMA protokolü önerilmiştir [8].…”
Section: İlgi̇li̇ çAlişmalarunclassified
See 1 more Smart Citation
“…Bir düğümün biri çok yakın diğeri çok uzak komşularının olduğu durumlarda farklı paket gecikmeleri yüzünden MACA'da çarpışmalar meydana gelebilir. [9]. Bu sorunun üstesinden gelmek için FAMA protokolü önerilmiştir [8].…”
Section: İlgi̇li̇ çAlişmalarunclassified
“…Çoklu-ACK mekanizmasının adapte edilmesi sayesinde bu sorun ortadan kaldırılmakta, maliyet ve enerji tasarrufu sağlanmaktadır. Bunun enerji, iş çıkarma oranı, gecikme ve güvenilirlik üzerinde olumlu etkileri vardır [9]. Bu bölümde Çoklu-ACK'da kullanılan ACK paket sayısı değişiminin iş çıkarma oranındaki iyileştirme ve enerji verimliliği üzerindeki etkileri irdelenmek üzere matematiksel ifadelere yer verilmektedir.…”
Section: Matemati̇ksel Anali̇zunclassified
“…Many proposed MAC protocols focus on UWSNs. [30][31][32] These protocols are proposed to overcome the effects of long propagation delay, such as low channel utilization, the hidden terminal problem, and the exposed terminal problem.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, UMMAC combines channel reservation and negotiation in order to reduce the overhead of time and energy, as well as utilize multiple channels to improve the network performance. Some other studies on efficient MAC protocol design for underwater sensor networks are found in [20][21][22][23][24][25]. While majority of previous studies focused on single-channel communications, a new trend has taken place to make use of multiple channels in UWSNs in recent years [26,27].…”
Section: Related Workmentioning
confidence: 99%